2022
DOI: 10.3389/fpsyt.2022.834425
|View full text |Cite
|
Sign up to set email alerts
|

Is the Therapeutic Mechanism of Repetitive Transcranial Magnetic Stimulation in Cognitive Dysfunctions of Depression Related to the Neuroinflammatory Processes in Depression?

Abstract: The lifetime prevalence of depression is reported to be >10%, and it is an important illness that causes various disabilities over a long period of life. Neuroinflammation process is often reported to be closely linked to the pathophysiology of depression. Approximately one-third of depression is known to be treatment-resistant depression (TRD), in which the symptoms are refractory to adequate treatment. Cognitive dysfunction is one of the most important symptoms of depression that impedes the rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…In research on mental disorders, the neuroiniflammation hypothesis has attracted much attention, so suppression of neuroinflammation is considered a possible strategy to treat mental disorders (Dey and Hankey Giblin, 2018;Li et al, 2022;Tateishi et al, 2022;Tayab et al, 2022). However, in recent years, due to the heterogeneity of factors underlying the pathogenesis of mental disorders, it has been suggested that mental disorders should be treated by a personalized medical approach (Yirmiya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In research on mental disorders, the neuroiniflammation hypothesis has attracted much attention, so suppression of neuroinflammation is considered a possible strategy to treat mental disorders (Dey and Hankey Giblin, 2018;Li et al, 2022;Tateishi et al, 2022;Tayab et al, 2022). However, in recent years, due to the heterogeneity of factors underlying the pathogenesis of mental disorders, it has been suggested that mental disorders should be treated by a personalized medical approach (Yirmiya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of pro-inflammatory cytokines derived from the over-activated innate immune cells have been repeatedly observed in patients with mental disorders such as depression (Yao et al, 2020;Ganança et al, 2021). Therefore, suppression of neuroinflammation has long been considered a potential strategy to treat mental disorders (Tateishi et al, 2022;Tayab et al, 2022). However, this view has been challenged by some other evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the significantly positive effect on the cognitive function of CKD patients, direct evidence is not well documented in the literature. One possible explanation is that caffeine may reduce the incidence of depression, which is more common in patients with CKD and is closely associated with cognitive impairment (48,49). Recent studies revealed that caffeine-derived metabolites could modulate the gut microbiota and improve depression (50).…”
Section: Discussionmentioning
confidence: 99%
“…Though most studies have targeted the motor cortex for pain management, several studies clearly showed significant analgesic effects following rTMS over the left dorsolateral prefrontal cortex (DLPFC 9 , 10 . During depressive episodes, low activity in the cognitive control network (CCN), which includes the dorsal anterior cingulate cortex (DAAC) and the DLPFC, has been found in resting functional connectivity in MDD patients 11 . Additionally, two studies found that rTMS applied over the DLPFC positively impacted cognitive function in healthy subjects and elders with mild cognitive impairment 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%